2018
DOI: 10.1016/j.cell.2017.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Human ADAR1 Prevents Endogenous RNA from Triggering Translational Shutdown

Abstract: Type I interferon (IFN) is produced when host sensors detect foreign nucleic acids, but how sensors differentiate self from nonself nucleic acids, such as double-stranded RNA (dsRNA), is incompletely understood. Mutations in ADAR1, an adenosine-to-inosine editing enzyme of dsRNA, cause Aicardi-Goutières syndrome, an autoinflammatory disorder associated with spontaneous interferon production and neurologic sequelae. We generated ADAR1 knockout human cells to explore ADAR1 substrates and function. ADAR1 primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
441
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 426 publications
(489 citation statements)
references
References 55 publications
44
441
4
Order By: Relevance
“…While some studies have suggested the possibility of ligandindependent activation of MDA5 (47), others have reported the role of endogenous dsRNAs, in particular those formed by inverted repeat Alu elements (IR-Alus), in constitutive activation of MDA5 (8). Similar IR-Alu-mediated activation was observed for wild-type MDA5 under the condition where the dsRNA-modifying enzyme ADAR1 (adenosine deaminase acting on RNA 1) is deficient (discussed below) (8,48). Recent studies showed that a chemotherapeutic agent, 5-aza-2 ′ -deoxycytidine, also activates MDA5 by upregulating endogenous retrovirus dsRNAs, leading to sterile inflammation that is beneficial for the subsequent cancer immunotherapies (49,50).…”
Section: Rig-i-like Receptorsmentioning
confidence: 88%
See 1 more Smart Citation
“…While some studies have suggested the possibility of ligandindependent activation of MDA5 (47), others have reported the role of endogenous dsRNAs, in particular those formed by inverted repeat Alu elements (IR-Alus), in constitutive activation of MDA5 (8). Similar IR-Alu-mediated activation was observed for wild-type MDA5 under the condition where the dsRNA-modifying enzyme ADAR1 (adenosine deaminase acting on RNA 1) is deficient (discussed below) (8,48). Recent studies showed that a chemotherapeutic agent, 5-aza-2 ′ -deoxycytidine, also activates MDA5 by upregulating endogenous retrovirus dsRNAs, leading to sterile inflammation that is beneficial for the subsequent cancer immunotherapies (49,50).…”
Section: Rig-i-like Receptorsmentioning
confidence: 88%
“…Accumulating evidence suggests that PKR can tolerate a certain level of structural irregularities (e.g., mismatches, bulges) in dsRNA (79) and can be activated by cellular dsRNAs under various physiological conditions. For example, in the absence of ADAR1, cellular dsRNAs formed by unmodified IR-Alu were proposed to activate PKR (48). Similarly, breakdown of the nuclear membrane during mitosis and consequent exposure of an excess amount of nuclear IR-Alus were also proposed to activate PKR (82).…”
Section: Protein Kinase Rmentioning
confidence: 99%
“…For example, although patients display a significant ISG signature, the molecular trigger that initiates the type I IFN response is not known. The study by Nakahama and co‐workers now joins other studies suggesting that self‐nucleic acids may trigger autoimmune diseases . Identifying the immunostimulatory self‐RNAs (presumably SINE RNAs or other endogenous RNA species) and investigating the molecular mechanisms by which ADAR1 prevents dsRNAs from activating PRRs could reveal insights into the underlying causes of various autoimmune diseases and clues on how to develop effective therapeutics.…”
Section: Adar1 Is Required For Thymic T Cell Maturation and Intestinamentioning
confidence: 89%
“…However, A-to-I editing also alters the RNA secondary structure, which may lead to recognition by innate immune receptors (Liddicoat et al, 2015;Pestal et al, 2015). Recent data have shown that ADAR1 predominantly edits Alu elements in RNA polymerase II (pol II)-transcribed mRNAs, but not those transcribed by pol III in human cells (Chung et al, 2018), and A-to-I conversion in Alus suppresses MDA5 activation in vitro (Ahmad et al, 2018).…”
Section: Adarmentioning
confidence: 99%